System-reliability-based disaster resilience analysis for structures considering aleatory uncertainties in external loads - Yi, Sang ri; Kim, Taeyong (Earthquake Engineering and Structural Dynamics, 2023)
The concept of disaster resilience is getting more prominent in the era of climate change due to the increase in the intensities and uncertainties of disaster events. To effectively assess the holistic capacity of structural systems, a disaster resilience analysis framework has been developed from a system-reliability-based perspective. The framework evaluates resilience in terms of reliability, redundancy, and recoverability and provides quantitative indices of reliability and redundancy for structures with a resilience threshold. Although this framework enables the comprehensive evaluation of disaster resilience performance, practical applications of such concepts to the structures subjected to dynamic excitations with large aleatory uncertainty, such as earthquakes, remain challenging. This study develops a framework to assess the resilience performance of structures by taking into account the aleatory uncertainties in external forces. Along with the development of reliability and redundancy curves that can effectively accommodate such excitations, a new resilience threshold representation is proposed to incorporate recoverability in the decision-making process. Moreover, we provide efficient procedures for calculating the reliability and redundancy curves to alleviate the computational complexity during the resilience analysis. Two earthquake application examples are presented targeting a nine-story building and a cable-stayed bridge system to demonstrate the enhanced practical applicability of the proposed framework.
Keywords: Aleatoric uncertainty; Aleatory uncertainty; Disaster resiliences; Earthquake excitation; Reliability-based; Resilience criteria; Resilience-based engineering; Structural system reliabilities; System reliability; Uncertainty; aleatoric uncertainty; earthquake excitations; resilience criteria; resilience-based engineering; structural system reliability